Case Report: Deep Brain Stimulation to the Ventral Internal Capsule/Ventral Striatum Induces Repeated Transient Episodes of Voltage-Dependent Tourette-Like Behaviors - Camprodon, Joan A.; Chou, Tina; Testo, Abigail A.; Deckersbach, Thilo; Scharf, Jeremiah M.; Dougherty, Darin D. (Frontiers in Human Neuroscience, 2021)
Deep Brain Stimulation (DBS) is an invasive device-based neuromodulation technique that allows the therapeutic direct stimulation of subcortical and deep cortical structures following the surgical placement of stimulating electrodes. DBS is approved by the U.S. Federal Drug Administration for the treatment of movement disorders and obsessive-compulsive disorder, while new indications, including Major Depressive Disorder (MDD), are in experimental development. We report the case of a patient with MDD who received DBS to the ventral internal capsule and ventral striatum bilaterally and presented with 2 weeks of voltage-dependent Tourette-like symptoms including brief transient episodes of abrupt-onset and progressively louder coprolalia and stuttered speech; tic-like motor behavior in his right arm and leg; rushes of anxiety, angry prosody, angry affect; and moderate amnesia without confusion. We describe the results of the inpatient neuropsychiatric workup leading to the diagnosis of iatrogenic voltage-dependent activation of cortico-subcortical circuits and discuss insights into the pathophysiology of Tourette as well as safety considerations raised by the case.